Hybrid conferences: opportunities, challenges and ways forward - Puccinelli, Eleonora; Zeppilli, Daniela; Stefanoudis, Paris V.; Wittische-Helou, Annaïg; Kermorgant, Marjorie; Fuchs, Sandra; Menot, Lénaïck; Easton, Erin E.; Weber, Alexandra A-T. (Frontiers in Marine Science, 2022)
Hybrid conferences are in-person events that have an online component. This type of meeting format was rare before the COVID-19 pandemic, but started to become more common recently given the asynchronous global progression of the pandemic, the uneven access to vaccines and different travel regulations among countries that led to a large proportion of participants being unable to attend conferences in person. Here we report the organization of a middle-sized (581 participants: 159 onsite, 422 online) international hybrid conference that took place in France in September 2021. We highlight particular organizational challenges inherent to this relatively new type of meeting format. Furthermore, we surveyed both in-person and online participants to better understand their conference experience and to propose improvements based on the feedback received. Finally, we compare the advantages and disadvantages of three types of conferences (onsite-only, online-only and hybrid) and suggest that hybrid events should be favored in the future because they offer the most flexibility to participants. We conclude by proposing suggestions and ways forward to maximize accessibility and inclusivity of hybrid conferences. Our study brings novel insights on the challenges and opportunities created by hybrid conferences, by reporting not only the organizing committee experience but also by considering the participants’ perspective.